Migration and Innovation - Does Cultural Diversity Matter for Regional R&D Activity? - Annekatrin Niebuhr (European Regional Science Association (ERSA), 2006)
Recent theoretical research deals with economic costs and benefits of cultural diversity related to immigration. Empirical evidence regarding the impact of cultural diversity on economic performance is still scarce. This paper aims at investigating the effects of diversity on innovation and at providing corresponding empirical evidence. We apply the knowledge production function approach to investigate the significance of cultural diversity of work force for innovation output. The regression analysis considers the determinants of regional innovation, focusing on the effect of diversity, for a cross-section of German regions in the period 1995 to 2000.
Keywords: 330